Children and their families the continuum of nursing care - Bowden, Vicky R.; Greenberg, Cindy Smith (Wolters Kluwer Health/Lippincott Williams & Wilkins, 2014)
Children and Their Families: The Continuum of Nursing Care is a comprehensive textbook about children's health care that can be used by both students and nurses in a variety of clinical practice settings. In developing this textbook, our goal was to provide the student and practicing nurse with the knowledge base that would enable them to make critical assessments and judgments regarding the child and his or her family in a variety of settings across the continuum of care. Today's pediatric nurse must be well versed in the numerous social, psychological, spiritual, and physical challenges facing youth and experts in managing complex acute and chronic conditions unique to children and adolescents"--Provided by publisher.